1999
DOI: 10.1123/tsp.13.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Can Associative and Dissociative Strategies Affect the Swimming Performance of Recreational Swimmers?

Abstract: This study examined the effects of association and both internal and external dissociation on the performance, perceived fatigue, and rate of exertion of recreational swimmers during two swimming trials. Before the first swim, 69 participants completed a self-report questionnaire. After the first swim, participants were assigned to one of four groups equated with swim performance times: control, associative, internal dissociative, and external dissociative groups. After completing both the first and second swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Experiment two also showed the superiority of an internal focus of attention over baseline and external conditions as well as elevated heart-rate levels in the internal condition, indicating that participants worked harder. A study by LaCaille, Masters, and Heath (2004) showed faster running times over 5 km when participants focused internally on their heart rate compared with focusing externally on music, and similar results were found in swimming (Couture, Jerome, & Tihanyi, 1999). These studies stand in contrast to those that show better performance in the external conditions like an early study in running (W. P. Morgan, Horstman, Cymerman, & Stokes, 1983) or more recent studies in swimming (Stoate & Wulf, 2011) and the running studies already described in more detail (Schücker et al, 2013;Schücker et al, 2009).…”
Section: Movement Efficiency and Endurance Performancesupporting
confidence: 61%
“…Experiment two also showed the superiority of an internal focus of attention over baseline and external conditions as well as elevated heart-rate levels in the internal condition, indicating that participants worked harder. A study by LaCaille, Masters, and Heath (2004) showed faster running times over 5 km when participants focused internally on their heart rate compared with focusing externally on music, and similar results were found in swimming (Couture, Jerome, & Tihanyi, 1999). These studies stand in contrast to those that show better performance in the external conditions like an early study in running (W. P. Morgan, Horstman, Cymerman, & Stokes, 1983) or more recent studies in swimming (Stoate & Wulf, 2011) and the running studies already described in more detail (Schücker et al, 2013;Schücker et al, 2009).…”
Section: Movement Efficiency and Endurance Performancesupporting
confidence: 61%
“…The association focus resulted in faster running but lower levels of positive affect than the dissociation focus. Other researchers have also reported better performance by athletes with an association focus in the sports of rowing (Connolly & Janelle, 2003) and swimming (Couture, Jerome, & Tihanyi, 1999). However, there have also been contrary findings (e.g., Morgan, Horstman, Cymerman, & Stokes, 1983).…”
Section: What This Paper Addsmentioning
confidence: 93%
“…Internal as well as external associative strategies resulted in a higher rating of perceived exertion levels (Stanley et al, 2007). Couture et al (1999) showed that swimmers using an associative strategy (thinking the word air when inhaling) swam significantly faster than the control group. Two further supporting studies were conducted in a rowing task (Scott et al, 1999;Connolly & Janelle, 2003).…”
Section: Associative and Dissociative Attentional Strategiesmentioning
confidence: 99%